A Cross-cultural and Buddhist-Friendly Interpretation of the Typology Exclusivism-Inclusivism-Pluralism - Vélez de Cea, Abraham (Sophia, 2011)
This article develops a new and expanded interpretation of the typology exclusivism, inclusivism, pluralism. The proposal refines the categories of what was originally a Christian typology in order to provide a truly cross-cultural and interreligious framework to better understand and compare the most common views of religious diversity found not only in Christianity, but also in Buddhism and other religions. Although building upon Schmidt-Leukel's logical reinterpretation of the typology, the article substantially modifies his framework and understands the typology, not as a comprehensive classification of possible attitudes toward other religions, but rather as an open-ended framework to clarify the nature of the most common theologies of religions that exist in reality. The new interpretation provides a more precise definition of inclusivism that does not conflate inclusivism with the affirmation of a singular maximum, thus distinguishing between absolutistic and non-absolutistic forms of inclusivism. The new interpretation introduces an intermediate position between inclusivism and pluralism called pluralistic inclusivism. The article challenges David Ray Griffin's concept of generic pluralism and proposes a new understanding of pluralism indebted to Raimundo Panikkar.